Hodnocení a řízení rizika při plánování vývojových projektů - Dobrovolschi, Olga; Olga Dobrovolschi (České vysoké učení technické v Praze, 2019)
Diplomová práce „Hodnocení a řízení rizika při plánování vývojových projektů“ se zabývá řízením projektových rizik při plánování projektů ve strojírenské společnosti. V teoretické částí se práce věnuje popisu pojmu rizika, risk managementu a analýze existujících metod používaných při analýze rizika. V praktické částí je návrh kvantitativní metody pro hodnocení rizika aplikovaný na konkrétní projekt výroby prototypů 3D tiskem. Práce poskytuje metodiku rizikové analýzy pro malé a střední podniky pro kvantifikace a hodnocení potenciálních projektových rizik v oboru.

Diploma thesis “Risk Assessment in the Planning of Development Projects” deals with project risk management in the planning of development projects in an engineering company. In the theoretical part, the thesis describes the concept of risk, risk management process and analysis existing methods used in risk assessment. In the practical part there is proposed a quantitative approach for risk analysis applied to a specific project of prototyping manufacture by 3D printing. The thesis provides a risk analysis methodology for SMEs to quantify and assess potential project risks in the industry.
Risk Assessment in the Planning of Development Projects
Keywords: Riziko; hodnocení rizika; analýza rizik; risk management; vývojové projekty; finanční dopad; Risk; risk management; risk analysis; quantitative risk assessment; Research & Development project; financial impact